LEAD-LAG DAN VOLATILITY SPILL OVER ALIRAN INVESTASI ASING PADA PERDAGANGAN SAHAM DI BURSA EFEK INDONESIA TAHUN 2009 – 2012 - Prasetyo, Dwi Hari (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
Along with the growing of economic development in Indonesia, IDX became one of promising capital market and hence, increase foreign investment inflow. As larger amount of foreign capital involved in stock market, it might cause the market become more vulnerable to shock. Potential damage may come from short run foreign investment, which is very responsive to any changes in market sentiments. This research conducted by using IDX daily market and foreign transaction data over the periode January 2009-December 2012 and employing Granger Causality test, Vector Autoregression, Impulse Response and Variance Decomposition. The result shows that there is bidirectional relationship between foreign investment and market return in IDX. Moreover, by employing EGARCH this research shows the existence of volatility spillover between foreign investment and market return. From the findings, it can be summarized that as foreign investment flowing in, it will increases the price of equity. However, foreign investment rushing out in large amount will give bad impact to the market return and make it worse by increasing market volatility.